Knockdown of Pin1 leads to reduced angiogenic potential and tumorigenicity in glioblastoma cells - (:unkn) unknown (SPANDIDOS PUBL LTD, 2015)
Glioblastoma is the most common and most aggressive type of primary brain tumor. Current approaches in the treatment of glioblastoma are not effective enough to increase patient survival or prevent recurrence following surgery. Consequently, the search for potential drug targets is ongoing. Peptidyl-prolyl cis/trans isomerase NIMA-interacting 1 (Pin1), an isomerase that is overexpressed in various tumors, has become an attractive molecule in cancer research. Pin1 has been reported to regulate proteins involved in essential cellular pathways that mediate cell proliferation, cell cycle progression, differentiation and apoptosis, by altering their stability and function. The results of the present study revealed that knockdown of Pin1 in glioblastoma cells using RNA interference or the selective Pin1 inhibitor, juglone, suppressed the tumorigenic features by reducing cell growth, migration and angiogenic potential. Furthermore, knockdown of Pin1 decreased the levels of vascular endothelial growth factor and matrix metallopeptidase 9, and also triggered apoptosis. Due to the fundamental roles of Pin1 in promoting tumorigenesis, Pin1 inhibitory molecules, including juglone, or alternative synthetic derivatives hold potential for the development of clinical countermeasures against glioblastoma.
Keywords: glioblastoma; tumorigenesis; peptidyl-prolyl cis/trans isomerase NIMA-interacting 1; juglone; vascular endothelial growth factor; PROLYL ISOMERASE PIN1; ENDOTHELIAL GROWTH-FACTOR; NF-KAPPA-B; SIGNALING PATHWAY; PROSTATE-CANCER; BREAST-CANCER; PROTEIN DAXX; EXPRESSION; APOPTOSIS; INHIBITION